Preoperative antibiotic prophylaxis in oral surgery Clinical study on 58 Iraqi patients (Mustansiria Dental Journal, 2018)
Preoperative prophylactic protocol in oral surgery is well established practice; stillit’s not used in Iraqi surgical centers. The aim of this study is to show thatpreoperative protocol is reliable surgical practice.58 patients, selected from the attendant of oral surgery clinic in Alkaramaspecialized dentistry center/Baghdad, were subjected to various oral surgicalprocedures 59 operations under local anesthesia. These patient were given single doseantibiotic prophylaxis preoperatively after we divide them into 3 groups, 1st groupwere given 1 gm amoxicillin (control group),second group were given 1 million i.u. ofprocaine penicillin; 3rd group were given 500 mg ampicillin vial,. The maximum timefor all procedures was 2 hours.We concluded that preoperative antibiotic prophylaxis can be used safely in outpatient’s oral surgical procedures, on Iraqi patient with minimum complications.